Implementation of Integrated Quality Management in Improving the Quality of School Library Services at SMPN 4 Sibulue, Bone Regency - Lestari, Sonia Eka; Wayong, Muhammad; Kasmawati, Kasmawati (Abjadia : International Journal of Education, 2025)
This study aims to analyze how the implementation of Total Quality Management (TQM) can be integrated within the context of educational institutions, particularly school libraries, to improve operational efficiency, customer satisfaction, as well as the overall management and governance of the library. This research employs a qualitative method with a phenomenological approach. The data analysis technique involves a systematic process of searching and organizing the results from interviews, notes, and collected materials to enhance understanding of all gathered information and to enable the presentation of findings. The results indicate that the library at SMPN 4 Sibulue faces challenges such as limited collections, facilities, and librarian competencies, which hinder optimal service delivery. To address these issues, the library implements systematic collection management, utilizes digital technology, establishes cooperative book procurement, and improves staff competencies through training. The school also strives to maximize space usage and proposes the acquisition of new facilities despite budget constraints. Strengthening staff mental and character development, literacy and digitalization training, and fostering a quality culture involving all parties are key factors, with regular monitoring and evaluation to ensure continuous service quality improvement in accordance with the principles of Total Quality Management.